ปัจจัยที่ส่งผลต่อการรับรู้ความสามารถในการใช้ภาษาอังกฤษ ของนักเรียนชั้นมัธยมศึกษาตอนปลาย - มูลศาสตร์ สุนทร; บวรกิติวงศ์ สุชาดา (An Online Journal of Education, 2018)
The purposes of this research were 1) to study the level of perceived English ability of upper secondary school students 2) to test the equality of perceived English ability among upper secondary school students who live in and didn’t live in Bangkok , Thailand. And 3) to develop and analyze the model of factors affecting perceived English ability among upper secondary school students. The samples of this research were 1,471 upper secondary student. The research instrument is a 5-rating scale questionnaire which its reliability is 0.939. The data were analyzed by arithmetic mean , t-test , chi-square , RMSEA , CFI , and SRMR. The research findings : 1) the level of perceived English ability of upper secondary school students is good. 2) the level of perceived English ability of upper secondary school students who live in and didn’t live in Bangkok , Thailand is not different significantly and 3) the model of factors affecting perceived English ability among upper secondary school students is fairly fit with the empirical data.